Biomechanics of gait in women with knee osteoarthritis - Roide, Leticia Yoko Nakamura de [UNESP]; Navega, Marcelo Tavella [UNESP]; Spinoso, Deborah Hebling [UNESP] (Elsevier, 2024)
Background Osteoarthritis is a chronic, progressive disease that affects more than 250 million people in the world, mainly women after menopause. Among all joints, the knee is the most commonly affected. Knee osteoarthritis (KOA) occupies tenth place in the world ranking of diseases that cause global disability. Walking is the most frequently performed daily task. Neuromuscular deficits characteristic of KOA, such as decreased quadriceps strength and balance, can lead to changes in the movement pattern during gait that contribute to greater energy expenditure and, consequently, limitation of the intensity and duration of this task. Objectives The study aimed to compare the kinematic variables of gait in women with and without KOA. Methods The study included 71 individuals divided into groups with Knee Osteoarthritis (KOAG, n=39; 66.8±7.7 years) and a control group (CG, n=32; 64.9±7.1 years). The study was approved by the local ethics committee and all participants signed an informed consent form. For gait evaluation, a 14-meter-long and 1-meter-wide walkway was used. The volunteers were verbally instructed to walk on the walkway at the same speed they were used to. Altogether, five attempts were made to evaluate gait. Kinematic data were obtained by Foot Switches (Noraxon®) pressure sensors, positioned bilaterally on the calcaneus and at the base of the hallux. The gait variables collected were support time; swing time; stride time; double support time and gait speed. For statistical analysis, the Multivariate Analysis of Covariance test (MANCOVA) was applied, using the co-variable gait speed. A significance level of p<0.05 was adopted. Results MANCOVA showed differences (p < 0.001) between the group with KOA (KOAG) and the control group (CG). In the KOAG group, the time of support, striding and double support was longer, representing, respectively, 17%, 8% and 33% higher in relation to the CG. The study showed that the KOAG had a shorter swing time and an 11% reduction in gait speed. Conclusion Women with KOA had an average speed 16% lower than the safe gait speed thresholds indicated in the literature (between 1.2 and 1.4 ms⁻¹) and alterations in the kinematic gait parameters, which can be interpreted as a strategy for reducing pain and joint overload on the knee while performing the task. Implications The study shows that women with KOA present a decrease in gait speed and alterations in the movement pattern that can negatively contribute to the level of functional mobility. Rehabilitation strategies for this population should include, in addition to resistance exercises, sensorimotor exercises to improve the gait pattern of this population.